LEXICAL COHESION OF ENGLISH â€“ LANGUAGE NEWSPAPERS IN INDONESIA - Yenni Arif Rahman (Jurnal Akrab Juara, 2019)
The study provides an empirical analysis on the use of lexical cohesion in English-langauge newspapers in Indonesia. Data for the study were 13 articles collected from 3 leading english-langauge newspapers in Indonesia. Halliday and Hassan seminal work of â€œCohesion inEnglishâ€provides a comprehensive taxonomy of lexical cohesive devices and Dooley and Levinsohn monograf gives the thorough examples how to analyse cohesive devices in the text. Of 424 lexical cohesive devices found in the samples, 171 (40. 3%) were repetition and 167 (39%) were collocation which are the most dominant lexical cohesive devices in the articles